2010
DOI: 10.1016/j.jvs.2009.08.091
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of public knowledge about the scope of practice of vascular surgons

Abstract: During the past decade, there has been a sharp increase in the number of vascular procedures performed in the United States. Due to the increase in the size of the aging population, this trend is predicted to continue. Despite this, general public knowledge about vascular surgery appears low. This gap may significantly affect the success of vascular surgery as a specialty. To objectively define knowledge about vascular surgery, we administered a questionnaire to both a sample of the general population and medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2010
2010
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…The VSQ is an instrument based on a previously validated survey. 6 It consisted of 56 questions (53 multiple choice and 3 short answer): 7 questions evaluated demographic information, 11 questions assessed the degree of student participation in the clerkship, 7 questions graded student experience during the rotation and interest in vascular surgery as a career, and 31 questions assessed knowledge of vascular disease and the role of the vascular surgeon in its management (Appendix, online only).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The VSQ is an instrument based on a previously validated survey. 6 It consisted of 56 questions (53 multiple choice and 3 short answer): 7 questions evaluated demographic information, 11 questions assessed the degree of student participation in the clerkship, 7 questions graded student experience during the rotation and interest in vascular surgery as a career, and 31 questions assessed knowledge of vascular disease and the role of the vascular surgeon in its management (Appendix, online only).…”
Section: Methodsmentioning
confidence: 99%
“…5 In addition, there exists a significant knowledge deficit about the role of the vascular surgeon as the caregiver in managing patients with peripheral vascular disease (PVD). 6 This knowledge deficit is present among the general population and may have a significant effect on how vascular surgeons are viewed by the public, the media, regulatory agencies, and other medical specialists. It also extends to medical students and may contribute to low interest in the choice of vascular surgery as a future career.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In one report, only about 50% of medical students knew that vascular surgeons operate on blood vessels, and only 24% knew that vascular surgeons treat non-healing wounds. 15) For motivating medical students to consider vascular surgery, different initiatives are required to expose them to vascular surgery. Some opportunities might include sponsoring medical students to attend national vascular meetings, including vascular surgery in introductory level medical classes, and sponsoring medical students' awards and presentations.…”
Section: Maintaining Open Operative Skills In the Era Of Endovascularmentioning
confidence: 99%
“…6 In another study, with the help of a questionnaire, Farber and colleagues showed a significant knowledge deficit among both the general population and medical students about the field of vascular surgery and, in particular, the daily work of a vascular surgeon. 7 All of these examples provide the necessary feedback for vascular surgical societies to create or adjust the course of their future strategies. The Society for Vascular Surgery (SVS) and the ESVS have both recently published guidelines for the management of carotid artery atherosclerosis.…”
mentioning
confidence: 99%